Restaurando a justiça criminal: a aplicação de práticas restaurativas em contextos retributivos de solução de conflitos criminais - Oliveira, Cássio Roberto Uruga (2024)
The idea of what justice is and how to achieve it is a permanent theme in Western political philosophy. Among the various thinkers who have committed to carrying out an analysis of justice, John Rawls and Amartya Sen provide theoretical substrates for an analysis of the paradigms for applying criminal justice. The retributive paradigm is the dominant paradigm and presents itself as a formal model of application of criminal justice that sees crime as a violation of established law and the State as the victim of the crime and exclusive holder of the right to punish. The restorative paradigm, which is the emerging one, returns the leading role in resolving the conflict to the parties involved and sees crime as a violation of social relations that needs to be restored. Despite presenting different foundations, principles and values, there is, in modern legal practice, a tendency towards concurrent application of the retributive and restorative paradigms for resolving criminal conflicts. Given this, the present work seeks to investigate the feasibility of applying restorative criminal justice in a way that competes with retributive criminal justice, in the context of Brazilian criminal justice. To this end, two research hypotheses were investigated: (i) it is possible to apply the restorative and retributive models of criminal justice application concurrently and this application can reduce the problems of the isolated application of the retributive model, achieving more efficient solutions. fair for criminal conflicts; and (ii) respecting the principles and values of restorative justice, the application of restorative justice in a manner that competes with retributive justice does not reduce the restorative potential of the practices applied, even though it is not the ideal solution to criminal conflicts. Thus, carrying out descriptive, qualitative and bibliographical research, using the deductive method, it was possible to verify that, analyzing the paradigms based on the justice theories of Rawls and Sen, the restorative paradigm presents better results than the retributive paradigm. Despite this, the paradigmatic transition is not yet possible due to the resistance inherent to this transition and the punitive culture still very present in Brazilian society. Thus, in the Brazilian judicial context, it is observed that the restorative and retributive paradigms have been applied concurrently, which finds support in Sen's theory, but would not be possible in Rawls' theory. This coexistence implies a series of precautions so that the dominant paradigm does not appropriate the emerging paradigm, limiting its application and distorting its institutes. Analyzing this problem, it was possible to identify three requirements for the application of restorative and retributive justice in a concurrent manner to be possible: respect for the principles and values of restorative justice, the limitation of retributive practices of traditional criminal justice and the constant monitoring of restorative practices applied. It is believed that respecting these requirements, the concurrent application of the restorative and retributive paradigms of justice will promote, in addition to a fairer solution to the conflict, an improvement in justice application institutions and a cultural change that may culminate in the adoption of the restorative paradigm. as dominant.